Study of some morphological and productive characteristics of the genus Foeniculum vulgare in three sites of Lattakia region (Latakia University Journal -Biological Sciences Series, 2021)
The research was carried out in some areas of Lattakia (Bahlouliyeh - Ras Shamra - Al Mzeraa) (different height from the sea level) in the agricultural season 2019-2020 with the aim of studying some morphological and productive characteristics of Foeniculum vulgare (plant height / cm, number of branches on the plant, total number of leaves, average Branch lengths / cm, number of inflorescences on the plant, average number of flowers / inflorescences, weight of 100 fruits / g, fruits weight in the inflorescence / g, plant fruits weight / g) to form a base upon which genetic improvement programs underpin the productivity of this plant. Where (10) samples were identified in each of the three sites, and each plant is 1-1.5 meters away from the other, and then the development of these plants was monitored and monitored periodically at a rate of once per week in different locations and in the stages of vegetative growth, flowering and maturity.The plants of Ras Shamra site were characterized by the highest values ​​with many characteristics: the height of the plant (320 cm), the number of branches on the plant (19), the number of inflorescences (18), and the weight of 100 fruits (0.39 g). While the plants of the Bahlouliyeh site were distinguished by the characteristics of the number of leaves (141), average lengths of the branches (98.74 cm), average number of flowers in the inflorescence (233), the weight of the fruits in the inflorescence (0.376 g) and the weight of the fruits in the plant (26.32 g.(The possibility of cultivating fennel at various altitudes (13-250m) from the sea surface, and with various types of soils in the Syrian coast, with preference to the sites of Bahlouliyeh and Ras Shamra.